Patterns and persistence of behavioural and psychological symptoms in those with cognitive impairment: the importance of apathy - van der Linde, Rianne M.; Matthews, Fiona E.; Dening, Tom; Brayne, Carol (Wiley, 2016)
Objective To study the stability and emergence of a range of behavioural and psychological symptoms (BPS), their association with mortality and the effect of covariates on these transitions in a population-based study of cognitively impaired older people with a long follow-up period and large sample size, with a particular focus on apathy.